The Role Of Early Children’s Education In The Growth Of Children Aged 4-6 Years : A Literature Review - Kurnia Yusuf; Aminuddin Syam; Healthy Hidayanty; Kadek Ayu Erika; Anwar Mallongi; Wahiduddin; Intan Sari Areni (International Journal of Medical Toxicology and Legal Medicine, 2024)
Objectives: This literature review examines the influence of stimulation and intervention of growth of children aged 4-6 years, as well as training on growth issues conducted by PAUD teachers. The review uses data from various studies to understand the role of PAUD teachers on the growth of children aged 4-6 years. The authors conducted a comprehensive search across multiple databases, including PubMed, MEDLINE, Science Direct, and ProQuest, for articles published between 2019-2024 . Results: A total of eight studies met the inclusion criteria . Regular monitoring of child growth by PAUD teachers is essential to detect developmental problems early on, so that appropriate interventions can be carried out. PAUD teachers are now more skilled in identifying child growth problems, thanks to increased knowledge through training and activities. With a better understanding of child growth and development, teachers can create an environment that supports optimal physical, social, and emotional development of children. Conclusions: Regular monitoring of child growth by PAUD teachers is important to ensure children’s physical growth according to age stages and to detect problems such as malnutrition. IEC training and activities can improve teachers’ knowledge in early detection of growth problems, so it is important to expand access to training and technology and encourage collaboration between teachers, parents, and medical personnel.